Peningkatan Kemampuan Penulisan Karya Ilmiah Internasional Bereputasi dengan Faktor Dampak yang Tinggi - Saprizal Hadisaputra; Gunawan Gunawan; Ilham Syahrul Jiwandono (Unram Journal of Community Service, 2020)
Lecturers must have the ability to conduct research and write scientific papers. This is very important both for the sake of itself and the interests of the Higher Education. However, most lecturers are constrained in terms of writing scientific papers because they have to go through a complicated process and require good scientific writing skills. These obstacles hampered lecturers from fulfilling the requirements for promotion, and also led to stagnation in increasing competence in the field of research and development of scientific works. This problem also occurs in the Teacher Training and Education Faculty (FKIP), Mataram University. Based on Sinta's data in 2019, the total number of scopus indexed article publications from FKIP Mataram University lecturers for 10 years was only an average of 4% of the total number of lecturers who published in international journals or seminars indexed on the indexer. The number of international publications is still low. Based on this, the FKIP Mataram University through the BP3MF Faculty of Research and Community Service Agency conducted training on article writing and publication techniques in international journals with the aim of improving the quality and quantity of research and community service carried out by lecturers. This is very necessary in order to improve the ability of lecturers in the field of research and development of scientific work at the FKIP, Mataram University. The method that will be used in this community service activity is Focus Group Discussion (FGD) in the form of training and mentoring to improve the ability of lecturers to write scientifically. The activity will be carried out in three stages, namely: (1) the planning stage, (2) the observation stage, (3) the implementation stage, (4) the evaluation stage. The service activity presents material, lectures, and discussions in delivering material consisting of: article writing, lecturer scientific writing framework, international journal publication techniques and the use of tools for language translation. The output of this activity is that participants gain important knowledge about improving their scientific writing skills. In addition, participants also gained broader insight into journal publication procedures at the international level